Materials and methods in ELT : a teacher's guide - McDonough, Jo; Shaw, Christopher; Masuhara, Hitomi (Chichester, West Sussex [England] ; Malden, MA : Wiley-Blackwell, 2013)
"Featuring extensive updates and revisions, the 3rd edition of Materials and Methods in ELT offers a comprehensive and useful introduction to the principles and practice of teaching English as a foreign/second language. A popular and practical guide for teachers, teachers in training, and for students studying methods and materials Features a new chapter on IT in English language teaching, new samples from current teaching materials, plus new sections on assessment and feedback, and on technology for materials and methods Covers how to approach materials and methods, evaluation and adaptation, technology for materials and methods, and teaching in under-resourced classrooms Examines the different methods available to teachers for organizing and managing an ELT classroom, including group and pair work, individualization, and classroom observation "--
"A popular guide for teachers, providing a comprehensive and useful introduction to the principles and practice of teaching English as a foreign/second language"--
Includes bibliographical references (pages 308-328) and index.
Keywords: English language -- Study and teaching -- Foreign speakers